(untitled) (Journal of Forensic Medicine & Toxicology, 2019)
Homicide is one of the heinous crimes against humanity and society, and it is as older as our civilization or history of humanity. The present study was carried out over a period of two years starting from November 2012 to October 2014 in the Department of Forensic Medicine, Govt. Medical College & Hospital Nagpur. Conclude that. From the study we concluded that Lacerated wound was predominant external injury (37.63 %) followed by abrasion i (34.40 %) and stab wound (33.33 %) among homicidal victims. Head and face were most vulnerable part of the body involved in 66.66 % of cases. Hard and blunt weapon was most commonly used weapon for homicide over head (46.23 %). While Sharp edged weapon were most commonly used in assault over thorax (30.1%) and abdomen (22.58%). Among internal organs cranio-cerebral organs (63.44%) were most commonly involved followed by lung (30.11%).